Liberalizm, neoliberalizm, wolność ekonomiczna i polityczna a rozwój gospodarczy kraju - Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The objective of this paper is to show that economic and political freedom is recognized as one of key determinants of the country’s economic growth. In its theoretical part, the definition, origins, and main ideas of neoliberalism were presented. Next section deals with the concept of economic freedom and its link with economic growth and development. Economic freedom indexes from both the Fraser Institute and the Heritage Foundation databases, as well as political freedom index from the Polity IV database were applied to assess the relationship between rate of economic growth and GDP per capita in Poland over the period 1990–2005. The results indicate that greater economic and political freedom contributes to higher GDP per capita values. However, opposite to political freedom, economic freedom did not serve as stimulus to higher rate of economic growth.